2020
DOI: 10.1177/1558925020935448
|View full text |Cite
|
Sign up to set email alerts
|

Silver ion release from Ag/PET hollow fibers: Mathematical model and its application to food packing

Abstract: A food packing system requires an antimicrobial environment with high air permeability to guarantee absolutely both food safety and long and reliable durability. A hollow fiber membrane containing silver ions is the best candidate for this purpose. However, a safe and controllable release process has become a pressing issue in the practical application. Here, we use the predator–prey model to predict the antimicrobial activity of silver ions released from a hollow fiber, and Staphylococcus aureus was applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…This paper focuses on artificial hollow fibers containing silver particles [14,15], with an emphasis on the release oscillation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This paper focuses on artificial hollow fibers containing silver particles [14,15], with an emphasis on the release oscillation [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Farahbod [2] established a mathematical model for diffusion and decomposition of pollutants, he found that the wave depletion plays an important role at the initial --------------stage. Lin et al [3][4][5][6] suggested a fractal diffusion oscillation for release of ions from a hollow fiber. Some researchers established a fractal differential models for diffusion-reaction processes.…”
Section: Introductionmentioning
confidence: 99%
“…The low frequency is also widely used in energy harvesting devices. [2][3][4] Additionally, many phenomena can be fully explained by the vibration theory; for example, the release oscillation [5][6][7][8][9] is the main factor affecting the ion release from a hollow fiber, while the thermal oscillation endows a cocoon with a particular bio-function. 10 The instability of a system also caught much attention to avoid any damage.…”
Section: Introductionmentioning
confidence: 99%